2022
DOI: 10.3390/catal12040445
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Study of Cu2O: Synthesis and Its Application in CO2 Reduction by Photochemical and Electrochemical Approaches

Abstract: Copper oxide (Cu2O) is a potential material as a catalyst for CO2 reduction. Cu2O nanostructures have many advantages, including interfacial charge separation and transportation, enhanced surface area, quantum efficiency, and feasibility of modification via composite development or integration of the favorable surface functional groups. We cover the current advancements in the synthesis of Cu2O nanomaterials in various morphological dimensions and their photochemical and electrochemical applications, which com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 80 publications
2
7
0
Order By: Relevance
“…The carbon source of the generated CO was verified by the 13 C labeling experiment. The primary signal at m/z = 28 is specified as 13 CO (Figure S5). These test results show that CO 2 is indeed the carbon source of CO in the photocatalytic reduction, which eliminates the possibility of CO formation on the surface of the photocatalyst in the system.…”
Section: Photocatalytic Activity and Electrochemical Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The carbon source of the generated CO was verified by the 13 C labeling experiment. The primary signal at m/z = 28 is specified as 13 CO (Figure S5). These test results show that CO 2 is indeed the carbon source of CO in the photocatalytic reduction, which eliminates the possibility of CO formation on the surface of the photocatalyst in the system.…”
Section: Photocatalytic Activity and Electrochemical Performancementioning
confidence: 99%
“…[3] Since the semiconductor catalysts were first reported in 1979, great progress has been made in the photoreduction of CO 2 . [4] TiO 2 , [5,6] CeO 2 , [7,8] BiOBr, [9,10] W 18 O 49 , [11,12] Cu 2 O, [13,14] ZnIn 2 S 4 , [15,16] Ag 3 PO 4 , [17,18] Ni 3 N, [19] Co 4 N, [20] Ni x Cu y , [21] TaON catalysts and their nanostructure components have been developed. Among all kinds of semiconductor photocatalysts, g-C 3 N 4 is a promising photocatalyst for CO 2 reduction with visible light response.…”
Section: Introductionmentioning
confidence: 99%
“…Among different types of candidates, such as transition metals, MOFs, COFs, polymers, and so on, transition metals have been preferred due to their different crystal phases, active centers, and tunable morphologies. In light of the above, copper has piqued our interest due to its viable oxidation states, reliable electron transmission, stability in the alkaline environment, ease in synthesis, and is highly abundant. In contrast to iron group metals, like Ni, Fe, and Co, Cu exhibits great electrical and thermal conductivity as well as a substantial resiliency to corrosion. Moreover, Cu is added to increase the catalytic activity by transferring electrons from Cu to other noble metals by reducing the d-band center of noble metals and weakening the adsorption energy. , Recently, Chen et al quantitatively studied the MOF-wrapped palladium nanocubes through XANES and observed the charge transfer from the Pd 4d bands to the Cu 3d (4sp)–O 2p hybridization bands of HKUST-1 at the Pd/HKUST-1 interface. Yu et al synthesized Cu nanowires with NiFe-layered double hydroxide nanosheets and studies the overall water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…Copperbased electrocatalysts can show excellent activity to convert CO 2 to C 2+ products via C-based radicals which can couple to afford C 2+ products. [5][6][7][8] Porous metal-organic framework (MOF) materials have emerged as efficient catalysts for CO 2 RR owing to the presence of atomically dispersed metal sites, and their porous structure allows adsorptive binding of CO 2 . [9][10][11][12] Several Cu(II)-based MOFs have been tested for electrochemical CO 2 RR, but they generally suffer from limited electrical conductivity and hydrolytic stability.…”
Section: Introductionmentioning
confidence: 99%